What Do We Know About Component Separation Techniques for Abdominal Wall Hernia Repair? - Scheuerlein, Hubert; Thiessen, Andreas; Schug-Pass, Christine; Köckerling, Ferdinand (Frontiers in Surgery, 2018)
Introduction The component separation technique (CST) was developed to improve the integrity of abdominal wall reconstruction for large, complex hernias. It is very difficult to compare the published findings because of the vast number of technical modifications to CST as well as the heterogeneity of the patient population operated on with this technique. Material and Methods The main focus of the literature search conducted up to August 2017 in Medline and PubMed was on publications reporting comparative findings as well as on systematic reviews in order to formulate statements regarding the various CSTs. Results CST without mesh should no longer be performed because of too high recurrence rates. Open anterior CST has too high a surgical site occurrence rate and henceforth should only be conducted as endoscopic and perforator sparing anterior CST. Open posterior CST and posterior CST with transversus abdominis release (TAR) produce better results than open anterior CST. To date, no significant differences have been found between endoscopic anterior, perforator sparing anterior CST and posterior CST with transversus abdominis release. Robot-assisted posterior CST with TAR is the latest, very promising alternative. The systematic use of biologic meshes cannot be recommended for CST. Conclusion CST should always be performed with mesh as endoscopic or perforator sparing anterior or posterior CST. Robot-assisted posterior CST with TAR is the latest development.